PENGARUH PROFITABILITAS, PERTUMBUHAN PENJUALAN, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUAMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2022 - Kasih, Kharisma Mutiara; Tulhusnah, Lusiana; Sari, Lita Permata (Fakultas Ekonomi dan Bisnis, 2025)
Food and beverage companies are currently experiencing rapid development because they are one of the needs of society in general. The increasing expansion is expected to provide contributions to society and companies. The aim of this research is Profitability, Sales Growth and Company Size on Company Value with Capital Structure in food and beverage companies as an intervening variable. This research uses quantitative research methods. The population in this study are companies listed on the indonesia Stock Exchange (BEI) with a sample of 9 companies. The sampling technique used in this research was purposive sampling. Data analysis and hypothesis testing in this research used the Structural-Partial Least Square Equation Model (PLS-SEM) method. The results of hypothesis testing regarding the direct impact of using Smart PLS 3.0, show that Profitability is significantly negative on Capital Structure, Sales Growth is negative but not significant on Capital Structure, Company Size is signicantly positive on Capital Structure, Profitability is positive not significant on Company Value, Sales Growth is positive but not significant to Company Value, Company Size is negative but not significant to Company Value, Capital Structure is Positive but not significant to Company Value. The results of the indirect influences hypothesis test show that the Profitablity variable is negative but not significant on Capital Structure through Company Value, Sales Growth is negative but not significant on Campital Structure through Company Value, Company Size is positive but not significant on Capital Structure through Company Value.